Frequency of Acetabulum Retroversion Formation after Reorienting Pelvic Osteotomies in Children Over 7 Years Old with Developmental Dysplasia of the Hip - P. I. Bortulev; S. V. Vissarionov; V. E. Baskov; D. B. Barsukov; I. Yu. Pozdnikin; T. V. Baskaeva (Travmatologiâ i Ortopediâ Rossii, 2021)
Background. One of the reasons for the development of the “pincer” type of femoroacetabular impingement are various reorienting pelvic osteotomies, which are widely used in the treatment of children with developmental dysplasia of the hip (DDH).